NUMERICAL ANALYSIS OF TUNNEL LED LIGHTING MAINTENANCE FACTOR - Cengiz, Mehmet Sait; CENGIZ, ÇIĞDEM (IIUM Engineering Journal, 2018)
ABSTRACT: It is necessary to periodically maintain lighting equipment in accordance with international standards. Contamination of lamps caused by long-term use of lighting equipment will result in loss of Luminous Flux and optical losses. The decrease in lighting performance poses a visual difficulty for drivers and causes accidents. In this study, the total Maintenance Factor is numerically examined by considering the losses of diffuser and lens for LED lamps used in tunnel lighting. The variation of luminaries performance with years considering Maintenance Factors as regards environmental conditions and features of the luminaries is evaluated to demonstrate the importance of tunnel lighting maintenance. Moreover, to show the importance of LED lamps Maintenance Factor, the variation of illumination levels of LED lamps is analysed under different Maintenance Factors. It is observed that enhancing Maintenance Factor would contribute to energy efficiency. ABSTRAK: Penjagaan peralatan cahaya secara berkala mengikut piawai kebangsaan adalah amat penting. Pencemaran lampu disebabkan penggunaan peralatan cahaya pada jangka panjang akan menyebabkan kehilangan kilauan kerdipan lampu dan optik. Pengurangan pencahayaan ini menyebabkan kesukaran pandangan pada pemandu dan menyebabkan kemalangan jiwa. Kajian ini mengkaji tentang jumlah Faktor Penjagaan secara numerik dengan mengambil kira pengurangan difuser dan kanta pada lampu LED yang digunakan dalam terowong pencahayaan. Faktor Penjagaan pada perubahan kilauan berdasarkan tahun mengambil kira keadaan sekeliling dan ciri khas kilauan. Tambahan, ini dinilai bagi menunjukkan kepentingan penjagaan terowong pencahayaan dan kepentingan Faktor Penjagaan Lampu LED. Perubahan pada tahap terang pada lampu LED dikaji dengan mengambil kira Faktor Penjagaan. Peningkatan pada Faktor Penjagaan telah didapati dapat menjimatkan tenaga.